Implementasi Prinsip Syariah pada Transaksi Foreign Exchange - Meilany, Merry; Khairunisa, Madona (Journal of Legal Sustainability, 2026)
The development of digital-based foreign exchange (forex) transactions is increasing along with technological advances and economic globalization. However, modern forex practices raise various issues from the perspective of Islamic Economic Law due to indications of usury, gharar, and maisir elements that contradict Sharia principles. This research is crucial to assess the implementation of Sharia principles in foreign exchange transactions so that currency exchange activities can be conducted in a halal, fair, and Islamic manner. This study aims to analyze the implementation of Sharia principles in foreign exchange transactions, the application of DSN-MUI Fatwa Number 28/DSN-MUI/III/2002, and the relevance of the al-sharf contract to modern digital-based forex practices. The research method used is qualitative research with a normative juridical approach through literature review. Data were obtained from the Quran, Hadith, DSN-MUI fatwas, books, scientific journals, and relevant previous research. The results indicate that forex transactions are permissible if they comply with the al-sharf principles and are free from elements of usury, gharar, and maisir. However, modern forex practices still face various challenges in implementing Sharia principles, particularly regarding the use of leverage, margin, and speculative activities in digital trading.